2019
DOI: 10.1080/09168451.2018.1559024
|View full text |Cite
|
Sign up to set email alerts
|

Supplemental feeding of phospholipid-enriched alkyl phospholipid from krill relieves spontaneous atopic dermatitis and strengthens skin intercellular lipid barriers in NC/Nga mice

Abstract: Plasmalogen (Pls) is a glycerophospholipid derived from alkyl phospholipid (Alk) with antioxidant functions in vivo. The present study investigated the effects of ether phospholipids, such as Pls and Alk, on intercellular lipid barriers in the skin of NC/Nga mice, a model of atopic dermatitis (AD). NC/Nga mice fed Alk showed increased plasma levels of Alk and Pls. The AD-related changes in ceramide composition in the skin were abrogated by oral administration of Alk. Moreover, Alk suppressed skin inflammation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…Additionally, a mouse model for atopic dermatitis (AD) was found to have increased levels of alkyl‐phospholipids while ceramides in the skin barrier were decreased. Interestingly, supplemental feeding of ether lipids could both restore ceramide levels and alleviate skin inflammation, pointing out how the levels of a specific lipid can be modulated by altering other lipid classes . In these lines, patients with Sjögren‐Larsson syndrome seem to have cutaneous and neurological symptoms which are thought to be a result of altered levels of ether phospholipids and sphingolipids .…”
Section: Crosstalk Of Ether Lipids With Other Lipid Classesmentioning
confidence: 99%
“…Additionally, a mouse model for atopic dermatitis (AD) was found to have increased levels of alkyl‐phospholipids while ceramides in the skin barrier were decreased. Interestingly, supplemental feeding of ether lipids could both restore ceramide levels and alleviate skin inflammation, pointing out how the levels of a specific lipid can be modulated by altering other lipid classes . In these lines, patients with Sjögren‐Larsson syndrome seem to have cutaneous and neurological symptoms which are thought to be a result of altered levels of ether phospholipids and sphingolipids .…”
Section: Crosstalk Of Ether Lipids With Other Lipid Classesmentioning
confidence: 99%
“…The functions of ether PLs in mammalian cells are still largely unknown, although there is increasing awareness of their importance in the regulation of membrane homeostasis and in cell signaling [27]. For instance, in a mouse model of atopic dermatitis, ceramide levels were decreased in the skin barrier, while supplemental feeding with ether lipids helped to alleviate skin inflammation [28]. Moreover, plasmalogens may function as endogenous antioxidants by protecting unsaturated membrane lipids from oxidation and scavenging reactive oxygen species (ROS) [29].…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with our results, changes in phospholipids were reported to be present in the serum of atopic patients compared with controls [ 57 ]. In another mouse model of AD, NC/Nga mice, phospholipids were decreased in plasma, and oral supplementation of plasmalogens increased the phospholipid concentration in the skin of the mice and improved the skin condition [ 58 ]. In human skin, one study reported an increase of phospholipid content in AD patients compared to healthy subjects [ 24 ], while others showed a global change in phospholipids with an increase in the presence of shorter acylated fatty acids [ 52 ].…”
Section: Discussionmentioning
confidence: 99%